A look at the financial returns of training: empirical evidence from textile sector of Pakistan. (1st January 2013) - Ahmed, Ishfaq; Ramzan, Muhammad; Khan, Muhammad Khalid
This research is aimed to provide empirical evidence of training effectiveness by using return on investment (ROI) as measurement tool. Fourteen textile composite units (listed in Islamabad Stock Exchange) were selected for study for two years: 2009 to 2011. Findings show that none of the respondents were using ROI of training as evaluation tool. So measuring training in financial terms using ROI would be something valuable for organisations. ROI was measured by estimating costs and benefits of training. Training costs comprised of four elements, i.e., trainer's fee, trainee's scholarship/fee, training development and delivery cost, and production lost during training time. Training benefits were divided in five categories, i.e., reduction in down time cost, reduction in errors, increase in production, reduction in repair cost, and savings from reduced absenteeism. Findings show that there is strong relation between training investments and benefits that organisations can reap. Findings also showed that all of the firms were having higher ROI than the costs associated with training. Implications and future implications are also given at the end.